Organizational integrity and its impact on enhancing organizational performance through psychological capital: an analytical study on a sample of employees of the general company for the oil industry in maysan governorate - Kazem, Jassim Rahi; Sabti, Yousif Mousa; Ali, Ghazanfar; Abbas, Yasir Abdullah; Nasser, Raed Hamid (International Journal of Rehabilitation and Special Education (IJRSE), 2021)
This research aims to know the impact of organizational integrity with its dimensions represented by (critical tasks, leadership supervision, focus on the process, focus on ensuring efficiency, human resource burden, communication and trust, education and continuous improvement, change) and its role in enhancing organizational performance in its dimensions represented by: (organizational, social) through psychological capital with its dimensions (self-efficacy, hope, optimism, and flexibility), in the general company for oil industry in Maysan governorate, as the research problem lies in the extent of the researched company’s interest in organizational integrity, the organization’s performance and psychological capital by deporting them. In addition to the extent of the relationship between them, and the importance of the research in diagnosing the impact of organizational integrity in its dimensions in enhancing the performance of the organization in its dimensions through psychological capital, and for the success of this research. A sample of employees in the general company for the oil industry in Maysan governorate was selected, and the researchers adopted on the questionnaire as a tool for data collection and to accomplish this research and achieve the objectives it seeks, (155) questionnaires were distributed, the researchers obtained (150) questionnaires, which are valid for statistical analysis. The statistical program (SPSS v.23) was used. The research reached a set of conclusions, the most important of which is that organizational integrity is one of the contemporary and important topics in the field of organizational behavior as a management philosophy used by organizations to achieve their goals.
Keywords: Organizational integrity; Organizational performance; Psychological capital